MOFs and MOF‐Based Composites for the Adsorptive Removal of Ciprofloxacin - Sriyanjali Bathula; Swathi Thottathil; Yashoda Malgar Puttaiahgowda (Macromolecular Materials and Engineering)
Abstract In spite of greater efforts to address antibiotic resistance, Ciprofloxacin (CIP) buildup in the aqueous medium continues to rise. The negative effects of CIP on the environment can be minimized through a comprehensive understanding of the technological advancements in removal techniques. The exploration of adsorbents like metal–organic frameworks (MOFs), activated carbon, porous organic polymers, etc., have found major usage in the adsorptive removal of antibiotics to tackle contamination. This study aims to compare the MOF‐based adsorbents and provide a guide to developing such materials for the successful removal of CIP. The isotherm models of the adsorbents are studied using Langmuir, Freundlich, Temkin, and Sips isotherms. Furthermore, pseudo‐second‐order, pseudo‐first order, intra‐particle diffusion, and Elovich models are used to study the kinetic models. The major mechanisms of adsorption, such as π–π interactions, H‐bonding, electrostatic interactions, hydrophobic interactions, and pore filling, are also analyzed. This study contributes to the future scope for the development of these MOFs for further exploration and applications in environmental remediation.